Effects of nebulized amphotericin B and budesonide inhalation for chronic cough-related laryngeal sensations. Issue 3 (June 2015) - Ogawa, Haruhiko; Fujimura, Masaki; Ohkura, Noriyuki; Makimura, Koichi
Abstract Objective To compare the acute effects of single nebulized amphotericin B and budesonide in treating cough-related laryngeal sensations in chronic cough patients, a randomized, single-blind, placebo-controlled, parallel-group trial was performed between two groups with positive and negative results of basidiomycetous (BM) fungi in their sputum culture. Methods Forty patients presenting with chronic cough lasting 8 weeks or longer, whose sputum could be obtained, were recruited for this study. At the first visit, all patients underwent fungal culture sampling of sputum, capsaicin cough inhalation test, pulmonary function tests, and cough-related laryngeal sensation questionnaire (C-LSQ) consisting of 6 items with a severity scale of 0–5 for each item: (1) a sensation of irritation in the throat (SIT); (2) tickle in the throat; (3) throat clearing; (4) urge to cough; (5) a sensation of something stuck in the throat; and (6) a sensation of mucus in the throat (SMIT). The patients were randomly assigned to receive either nebulizer inhalation of 2.5 mg of amphotericin B (Group A) or nebulizer inhalation of 0.5 mg of budesonide (Group B). The efficacies of each therapy were estimated by the change in C-LSQ score. Results There were significant differences in the delta score of item 1 (SIT) and item 2 in the BM-negative group and item 6 (SMIT) in the BM-positive group at 60 min after inhalation between Groups A and B (P < 0.05). Conclusion The results of this study suggested that appropriate use of single inhalation of budesonide or amphotericin B, which would be selected based on the results of sputum culture, may lead to suppression of cough-related laryngeal sensations, such as SIT or SMIT.